Creating stimulus materials for scientific research in application builder NeoBook - Liovkin V. E. (Educational environment today: development strategy, 2018)
Applying experimental methods in social and humanitarian sciences is complicated both because of specifics of the research subject (activeness and development of psychic and cultural reality) and because of researchers' not-awareness about the possibilities of modern IT which support controlling necessary variables. In this paper we suggest an instrument used in Tyumen State University for several years - NeoBook - rapid application builder. It can be used by not programmers for developing software for constitutive and forming research. On the example of the investigation of visual perception with the help of programmed tachistiscope we demonstrate effective and easy way to provide experimental research with stimulus material. Following the instructions in the article everyone can create programmed tachistiscope even if it is your first experience of programming in NeoBook.
Keywords: NeoBook; NeoBook; programming for beginners; стимульный материал; программирование с нуля; тахистоскоп; информатика для гуманитариев; Stimulus material; experiment in humanitarian and social science; tachistiscope; IT for humanitarians; эксперимент в общественных науках; эксперимент в гуманитарных науках